Appraising the life cycle costs of heating alternatives for an affordable low carbon retirement development. (February 2022) - Mohammadpourkarbasi, Haniyeh; Sharples, Steve
Graphical abstract: Highlights: 4.5 times more energy is required for heat compared to regulated electricity. ASHP and SHW scenario had low energy, maintenance, and overall operational costs. ASHP and SHW had very low CO2 e emissions but the highest capital costs. Heat incentives and applying carbon tax would reduce the payback time of renewables. Projection of future carbon intensity and cost of electricity is essential for life cycle analysis. Abstract: This paper assesses the low carbon design of housing developments for retired people who are willing to downsize. There is a need for a strategic approach to provide energy-efficient housing in general, but specifically for a growing aged population. This approach should be inclusive and affordable. Therefore, this study assessed the capital and operational costs of space and water heating of typical UK retirement dwellings by considering over a 30-year life cycle, the use, maintainability, replacement frequency, and sustainability of applying different low carbon energy technologies and renewables to various primary heating plants. Conventional heating systems (e.g. gas, electricity) and low carbon green technologies, such as photovoltaics (PV), solar hot water systems (SHW), combined heat and power (CHP) and air source heat pumps (ASHP), were studied and compared. A combination of ASHP and a SHW system reduced the energy costs by 57% maintenance costs by 14% and produced 46% lower carbon emissions than the gas boiler option. However, the ASHP option generated 75% more capital costs than the gas boiler scenarios as well as high replacement costs due to the short life expectancy of the system. The gas boiler and PV combination had the lowest capital, energy, and life cycle costs but also hadhigh carbon emissions. The results suggest that UK government incentives, such asapplying a carbon tax would significantly reduce the payback time of green technologies and could, therefore, be the key drivers of low carbon adoption.